Green Economic Development: Opportunities and Obstacles for Developing Countries - Rachmawati, Meida (International Journal of Law Social Sciences and Management, 2026)
This research analyzes the implementation of green economy in developing countries as an alternative development paradigm that integrates economic, social, and environmental aspects. The research methodology employs a qualitative approach with literature analysis from various primary and secondary sources. The results show that developing countries have significant opportunities in green economy through renewable energy investments, environmentally friendly technologies, and green job creation. Indonesia successfully attracted green investments worth US$1.6 billion in 2023, up 28% from the previous year. However, major barriers include limited initial capital, inadequate infrastructure, and human resource capacity constraints. South Korea demonstrated successful green economy transition by obtaining economic benefits of US$1.6 billion and creating 3,000 green jobs within five years. The research concludes that green economy implementation requires an integrative strategy including supportive fiscal policies, international partnerships, and institutional capacity strengthening to achieve inclusive and environmentally friendly development.